Aeromonas salmonicida isolates: Attachment ability and sensitivity to four disinfectants. (June 2018) - Qi, Jun; Wang, Huawei; Cai, Linlin; Wang, Huhu; Xu, Xinglian; Zhou, Guanghou
Abstract: Aeromonas spp. are closely associated with food spoilage, and often enter the food chain through cross-contamination during processing from biofilms on food-contacted surfaces. The attachment abilities of two high-spoilage Aeromonas salmonicida isolates were compared. The sensitivities of these isolates in biofilm to four disinfectants, namely sodium hypochlorite, chlorine dioxide, acidic electrolyzed water (AEW) and neutral electrolyzed water (NEW), were assayed. The results indicated that isolate 1425 showed higher attachment ability as compared to isolate 1435 at initial attachment (30 min) under a short-term attachment scenario (5 h), reaching more than 5 log CFU/cm 2 . Under a long-term attachment scenario (7 days), isolate 1425 formed a mature biofilm after 5 days of incubation, with the highest observed cell numbers of nearly 9 log CFU/cm 2 . The dynamics of biofilm formation of isolate 1435 were relatively stable, with cell population ranging from 6.25 to 7 log CFU/cm 2 . The composition of the extracellular polymeric substances and the morphology of the mature biofilm were identified by Attenuated Total Reflection Fourier Transform Infrared spectroscopy (ATR-FTIR) and Confocal Laser Scanning Microscopy (CLSM). The mature biofilm formed by isolate 1425 showed more resistance to tested disinfectants than that of isolate 1435. Sodium hypochlorite (200 mg/L) and AEW (40 mg/L) showed greater lethal effects than the other disinfectants. Moreover, 40 mg/L of AEW was as effective as 200 mg/L of sodium hypochlorite. These findings indicated that the biofilm formed by microorganisms associated with food spoilage and safety could not be ignored during food processing and that AEW may be a promising alternative to sodium hypochlorite for the elimination of such biofilms. Highlights: Biofilm formation of A.salmonicida was assessed under two contamination scenarios. The resistance of formed-biofilm was strain-dependent and disinfectant-dependent. AEW may be a promising alternative to sodium hypochlorite for combating biofilm.